Eksistensi Pancasila Sebagai Dasar Negara Indonesia - Cesilia Fransiska H Rajagukguk; Dian Novita Ayudea; Encik Mutia Rama Ananda (Pusat Riset dan Inovasi Nasional, 2024)
this article examines the existence of Pancasila as the basis of the Indonesian state by focusing on the role and application of pancasila in shaping national identity in Indonesia.Pancasila as the basis of the state is very necessary for the people of Indonesia to maintain harmony among the people in accordance with the personality of the Indonesian nation that is reflected in Pancasila. This study also evaluates the challenges faced by Pancasila as the basis of the state. The results of this study show that despite facing various challenges, Pancasila remains relevant as the foundation of the country, also plays an important role in maintaining national unity and stability. This study uses a literature study method that is based on various sources such as books, journals and articles. Thus, the existence of Pancasila as the basis of the Indonesian state is very influential on the behavior of the people of Indonesia.